Innovation Modification During Intraorganizational Adoption - Lewis, Laurie K.; Seibold, David R. (Academy of Management Review, 1993)
We propose a theoretical framework illustrating key sets of constructs and processes, both at the individual level and at the organization level, that constitute the intraorganizational adoption of innovations. It illustrates how socialization, social influence, and structuration processes in organizations operate to influence the degree of fidelity (match between design/intended use and actual use) and uniformity (similarity across users) in innovation process outcomes. We offer propositions concerning how innovations come to lack fidelity and/or uniformity as they are used in organizations. A case study of a program innovation in a Fortune 400 corporation is used to illustrate the framework.